Investigating Microstructural Abnormalities and Neurocognition in Sub-Acute and Chronic Traumatic Brain Injury Patients with Normal-Appearing White Matter: A Preliminary Diffusion Tensor Imaging Study - Hashim, Eyesha; Caverzasi, Eduardo; Papinutto, Nico; Lewis, Caroline E.; Jing, Ruiwei; Charles, Onella; Zhang, Shudong; Lin, Amy; Graham, Simon J.; Schweizer, Tom A.; Bharatha, Aditya; Cusimano, Michael D. (Frontiers in Neurology, 2017)
For a significant percentage of subjects with chronic traumatic brain injury (TBI) who report persisting cognitive impairment and functional loss, the diagnosis is often impeded by the fact that routine neuroimaging often doesn’t reveal any abnormalities. In this paper, we used diffusion tensor imaging (DTI) to investigate the apparently normal white matter (as assessed by routine MRI) in the brains of 19 subjects with sub-acute (9) and chronic (10) TBI of all severities. We also assessed memory, executive function, and visual-motor coordination in these subjects. Using a voxel-wise approach, we investigated if parameters of diffusion were significantly different between TBI subjects and 17 healthy controls (HC) who were demographically matched to the TBI group. We also investigated if changes in DTI parameters were associated with neuropsychological performance in either group. Our results indicate significantly increased mean and axial diffusivity (MD and AD respectively) values in wide spread brain locations in TBI subjects, while controlling for age, sex, and time since injury. and fractional anisotropy (FA) and increased radial diffusivity (RD) values. HC performed significantly better than the TBI subjects on tests of memory and executive function indicating the persisting functional loss in chronic TBI. We found no correlation between diffusion parameters and performance on test executive function in either group. We found bi-directional correlations between FA and memory, and positive correlation between RD and visuo-motor coordination test, in various tracts in both groups. Our study suggests that changes in MD and AD can indicate persisting micro-structure abnormalities in normal appearing white matter in the brains of subjects with chronic TBI. Our results also suggest that FA in major white matter tracts is correlated with memory in health and in disease alike; larger and longitudinal studies are needed to discern potential differences in these correlations in the two groups.